اختصاصات هيئات الرقابة المستقلة في العراق : التعارض والتداخل - عبدالأمير، علي حسن (الجامعة المستنصرية - كلية القانون, 2010)
الفاسدون يعملون دائمًا على تطوير قدراتهم وتحسين وسائلهم مما يجعل الأجهزة التقليدية غير قادرة على كشفهم، لذلك بادرت العديد من دول العالم المتحضر إلى إنشاء جهاز متخصص في مكافحة الفساد يتلقى اتهامات بالفساد والتحقيق بها، ويرفع تقاريره إلى الأجهزة التشريعية في الدولة وينشر تقاريره الدورية، كما يجب أن يقوم بدور لا يقل أهمية وهو تنفيذ حملات توعية عامة وتثقيف المجتمع لتجنب الوقوع بالفساد والإبلاغ عن الفاسدين. \ \ وقد أعطت الدول الحق لهذه الأجهزة التدقيق في جميع حالات الاشتباه في سوء استخدام الوظيفة العامة من قبل أي كان، للحصول على رشوة أو ممارسة الوساطة أو المحاباة أو استخدام الموارد العامة أو تبذيرها على نفسه أو على جماعته أو منح بعضها من دون وجه حق للآخرين، مقابل الحصول على منافع. \ \ كما يحق لهذه الأجهزة الإطلاع والتحقيق في ممارسة وسلوك الأجهزة الأمنية في حال الاشتباه في سلوك فاسد، مع احترام إجراءات الإطلاع والمحافظة على خصوصية الأفراد وسرية المعلومات. \ \ إن هذه الأجهزة الرقابية وهي في سبيل أداء مهامها تضع إستراتيجية وطنية متكاملة للتصدي للفساد ومواجهته في المجتمع، وصولًا إلى بناء نظام نزاهة وطني. \ \ ولا يفوتنا في هذا المقام أن نذكر حق هذه الأجهزة بمراجعة التشريعات واللوائح والنظم واقتراح تطويرها لضمان تجريمها للإثراء غير القانوني ومحاصرة منابع الفساد المالي والإداري. That the corrupt will always work to develop their potential and improve their methods, which makes conventional devices are unable to pay the bill, so it has initiated many countries of the civilized world to the establishment of a specialized anti-corruption receives allegations of corruption and investigation, and reporting to the legislature in the country and publishes periodic reports, as must play a role no less important is the implementation. \ of public awareness campaigns and educate the community to avoid corruption and reporting on the corrupt. \ Has given states the right to those services to look into all cases of suspected misuse of public office by anyone, for a bribe or the practice of mediation, nepotism or the use of public resources or squandered on himself or his group or to grant some of them unlawfully to others, compared to access to the benefits. \ Shall also be entitled to those services available and to investigate the practice and conduct of security services in the event of suspected corrupt conduct, while respecting the procedures for consulting and the preservation of individual privacy and confidentiality of information. \ These regulatory agencies are performing their duties in order to develop an integrated national strategy to tackle corruption and respond in the community, to building a national integrity system. \ Aevotna and in this regard to remember that the right of these agencies to review legislation, regulations and systems and the proposal developed to ensure the criminalization of illegal enrichment and trapping the sources of financial and administrative corruption.
Keywords: العقوبات -- الفساد الإداري -- مكافحة الفساد -- الرقابة الادارية -- جرائم الرشوة -- القوانين والتشريعات